Analisis Tingkat Kebutuhan Kompetensi Komunikasi Bahasa Inggris Martim pada Kegiatan Olah Gerak dan Pengendalian Kapal - Kumara, Rahindra Bayu; Dillyanto, Prijantono; Sutantyo , Erwin; Purwanto, Purwanto (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2024)
In the period of 2014-2021, the Annual Overview of Marine Casualties and Incidents (EMSA, 2022) shows the number of ship accidents with a total of 535 incidents, 34% of which were 182 merchant ship collisions. On the accidents at sea, almost 60% are caused by human error which is partly based on seafarer competency, fatigue, implementation of safety culture, and communication interpretation skills. Communication skills influence to the human error factor, so efforts are needed to improve communication skills using maritime English to reduce the potential for ship accidents. This research analyzes the level of communication needs in using maritime English to support ship maneuvering and control activities by sailors. This research consisted of 66 respondents from 5 shipping industries with 4 main components that support navigation tasks and functions in ship movement and control, namely components A, B, C, and D. The method used in this research is a descriptive quantitative and the data was obtained by distributing questioner by Google form. The results of the study show that the average value of components A, B , C, and D respectively are 4.31 in the